Clinical features of epileptic syndrome and alteration of NMDAand of AMPA-receptors of glutamate in the pathogenesis of the disease in the patients with supratentorial meningiomas of the brain - V. N. Ochkolyas; A. A. Skoromets; A. F. Gurchin (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2018)
Forty three patients with supratentorial meningiomas were under examination. A significant increase of the level of autoantibodies to the GluR1 -subunit of the AMPA-receptors of glutamate was seen in the patients with meningiomas with epileptic syndrome. The maximal level of the autoantibodies to the GluR1-subunit of the AMPA-receptors of glutamate is registreted under the effect of the tumor on the frontal and temporal lobes.